ANALISIS FAKTOR-FAKTOR PENYEBAB REWORK PADA PROYEK KONSTRUKSI GEDUNG DI KOTA PAYAKUMBUH - Seprizal Seprizal; Dedi Kurniawan (Ensiklopedia Research and Community Service Review, 2022)
The key to project success depends on four factors, including the project running according to the contract schedule, getting profits because expenses are as planned, problems that occur in the project are small, and there are no work accidents. If the technique used is not good, it will have a negative impact on project performance and can cause losses in terms of cost, quality, and time. The purpose of this study was to determine the factors that cause rework and what are the dominant factors that cause rework in the implementation of building construction projects in Payakumbuh City. The tests carried out include validity, reliability, and descriptive analysis based on mean values with the help of the Statistical Package for Social Science (SPSS) for Windows version 21.0 programme.This research identifies 10 factors that cause rework, the factor of lack of team work, the factor of wrong decision making, the factor of using tools that are not correct or not according to their function, the factor of the situation drawn with the field does not match. The factor of poor information flow from related parties, the factor of weak supervision of technical specs, the weather factor that causes delays in project implementation, the factor of incomplete contracts, the factor of acceleration due to owner requests, the factor of unexpected underground conditions. The results showed that the most dominant factor causing rework was the factor that the situation in the drawing did not match the field with a mean value of 3.90.